A Gluco-Mindful Approach To Diabetic Gastroparesis - Sanjay Kalra; Saptarshi Bhattacharya; Hitesh Punyani (Journal of the Pakistan Medical Association, 2024)
Diabetes gastroparesis is a common manifestation of autonomic neuropathy in persons with long-standing, uncontrolled diabetes. Most discussion about its management revolves around the mitigation of symptoms. Here, we share tips on choosing the right glucose-lowering medication, based upon predominant symptomatology of gastroparesis. We highlight about insulin preparations, and their timing of administration, can be tailored according to need. We also emphasize the need to choose oral glucose lowering drugs with care. KEYWORDS: FI Asp, GLP1RA, modern sulfonylureas, person-centred care, SGLTi, tirzepatide, URLi